Star formation time-scale in the molecular filament WB 673. Issue 4 (1st November 2022) - Ryabukhina, O L; Kirsanova, M S; Henkel, C; Wiebe, D S
ABSTRACT: We present the observations of ammonia emission lines toward the interstellar filament WB 673 hosting the dense clumps WB 673, WB 668, S233-IR, and G173.57+2.43. LTE analysis of the lines allows us to estimate gas kinetic temperature (≲30K in all the clumps), number density (7–17 × 10 3  cm −3 ), and ammonia column density (≈1–1.5 × 10 15  cm −2 ) in the dense clumps. We find signatures of collapse in WB 673 and presence of compact spatially unresolved dense clumps in S233-IR. We reconstruct 1D density and temperature distributions in the clumps and estimate their ages using astrochemical modelling. Considering CO, CS, NH3, and N2 H + molecules (plus HCN and HNC for WB 673), we find a chemical age of t chem  = 1–3 × 10 5  yrs, providing the best agreement between the simulated and observed column densities in all the clumps. Therefore, we consider t chem as the chemical age of the entire filament. A long preceding low-density stage of gas accumulation in the astrochemical model would break the agreement between the simulated and observed column densities. We suggest that rapid star formation over a ∼10 5  yrs time-scale take place in the filament.